EFEKTIVITAS SEDIAAN PATCH EKSTRAK DAUN SIRIH MERAH (Piper crocatum) SEBAGAI PENYEMBUHAN LUKA BAKAR DERAJAT II SECARA IN VIVO - Amelia, Rosa; Trinovita, Elsa; Patricia, Tisha; Fatmaria; Handayani, Septi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Burns are a health problem that is often faced in Indonesia with a high incidence rate. One approach that has been taken in treating burns is using natural medicines. The red betel plant (Piper crocatum) has the potential as an anti-inflammatory and wound-healing agent. Transdermal patch preparations are an alternative form of drug dosage with various advantages. This study aims to evaluate the effectiveness of red betel leaf extract patches in healing second-degree burns in vivo. Patch preparations were made with several different formulations, and evaluations were carried out on the patch preparations. The treatment groups were carried out on male white rats of the Wistar strain, which were divided into four groups of red betel leaf extract patch formulations. Treatment was carried out for 14 days. Several parameters to assess effectiveness for healing second-degree burns include moisture, color, and scab. The results of the LSD posthoc test showed that there was a difference in the mean between treatment groups with significant healing of burn wounds in mice (p-value < 0.05). The F4 red betel leaf extract group (30%) showed the highest healing value of 50.37%. Red betel leaf extract (Piper crocatum) is effective in healing second-degree burns in vivo.